KARAKTERISASI GEOKIMIA UNSUR MAYOR DAN UNSUR JEJAK PADA PUMICE HASIL ERUPSI KALDERA MANINJAU, SUMATERA BARAT - Nahdatul Zakkiyah; Hamdi Rifai; Harman Amir; Fadhila Ulfa Jhora (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Pumice is a silica-rich volcanic product that provides important information on magma characteristics and petrogenetic processes. This study aims to characterize the major and trace element geochemistry of Pumice from the Maninjau Caldera, West Sumatra. Pumice samples were analyzed to determine their major and trace element compositions and interpreted based on magma geochemistry. The results show that the Pumice is dominated by SiO₂ (75.33%) and Al₂O₃ (17.46%), whereas K₂O, Fe₂O₃, CaO, and TiO₂ occur in lower concentrations. Trace elements are dominated by Th, Rb, and Sr, while Zr, Y, and Nb occur in relatively low amounts. These geochemical characteristics indicate that the Pumice originated from felsic magma with rhyolitic to dacitic composition that experienced advanced magmatic differentiation through crystal fractionation, particularly of plagioclase. This study demonstrates that pXRF is an effective, rapid, efficient, and non-destructive method for preliminary geochemical characterization of volcanic rocks.